DOI: 10.31274/rtd-180813-16602
|View full text |Cite
|
Sign up to set email alerts
|

Virtual design for the interactive placement of baffles in air flow

Abstract: Appendix A1. Star-CD TM script for running simulation without Closed Baffle checked on a Windows OS Appendix A2. Star-CD TM script for running simulation with Closed Baffle checked on a Windows OS iii Appendix A3. Star-CD TM script for gather post-processing Information 64 Appendix A4. Code to create cell and vertex files representing baffles in Star-CD TM 65

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Many systems require the expertise of an analysts to be able to interpret the resultant data further removing the user from how their solution came to fruition. 44 It was suggested that the link between computers and humans could be strengthened to allow engineers to more readily and easily solve engineering problems without being constrained by the knowledge of the computer code, graphics, or the numerical tools necessary to solve difficult engineering problems. Today, the tools that exist allow full immersion into engineering environments where modeling and testing is done together.…”
Section: Problem Solving Environmentmentioning
confidence: 99%
“…Many systems require the expertise of an analysts to be able to interpret the resultant data further removing the user from how their solution came to fruition. 44 It was suggested that the link between computers and humans could be strengthened to allow engineers to more readily and easily solve engineering problems without being constrained by the knowledge of the computer code, graphics, or the numerical tools necessary to solve difficult engineering problems. Today, the tools that exist allow full immersion into engineering environments where modeling and testing is done together.…”
Section: Problem Solving Environmentmentioning
confidence: 99%
“…This research also discusses extending the ability to do shape optimization interactively with high-fidelity models that require intricate meshing routines and model preparation [Abodeely 2007, Engelbrecht 2007. The benefit of this is that shape optimization tools provide significant capability to design engineers to solve complex problems on their desktop.…”
Section: Problem Solving Environmentsmentioning
confidence: 99%